PREDICTORS OF HOTEL GUESTS’ LOYALTY: INVESTIGATING THE ROLE OF SHARIAH COMPLIANT HOTEL (SCH) PRACTICES AND HOTEL GUESTS’ ACCEPTANCE - Othman, Nur Zalikha; Mohd Isa, Salmi; Thurasamy, Ramayah (Malaysian Journal of Business and Economics (MJBE), 2020)
Guest loyalty is a major consideration for hotel competitive advantage. To be sustaining in this competitive market, hotel organization need to differentiate their business with their competitors. The new concept and new experience of SCH will capture guest attention that really concerns on halal, food safety and hygiene. SCH practices have discovered significant influence towards customer awareness, guests’ perception, perceived values, attributes and challenges. Thus, the purpose of this study is to examine the relationship between SCH practices, hotel guests’ acceptance and hotel guests’ loyalty. Data for this study were gathered through self-administered questionnaires on 420 hotel guests’ who have had experienced staying in 45 Five-star rated hotels in Malaysia. PLS-SEM was performed to analyse the proposed hypotheses. Findings showed that SCH practices have significant positive effect relationship on hotel guests’ acceptance and hotel guests’ loyalty. Hotel guests’ acceptance has also been found to be significant mediator of the relationship between SCH practices and hotel guests’ loyalty. Theoretical and practical implications of the findings were discussed. Limitations and future research approaches were forwarded.